Egg introduction during complementary feeding according to allergic risk: not just for peanuts! - Elvira Verduci; Annamaria Bianchi; Marta Brambilla; Mauro Calvani (BMC, 2018)
Abstract The relationship between the timing of introduction of complementary foods and later allergy is a topic of current discussion. Although the European Society for Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) has recently recommended that potentially allergenic foods may be introduced when complementary feeding is commenced, any time after 4 months, recommendations about egg introduction would be needed mainly for infants with high risk of developing food allergy. Before the first administration in these infants an adequate topical therapy and an evaluation of whole egg-specific IgE serum antibody levels or skin prick tests for egg should be recommended.